2020
DOI: 10.3390/jcm9103258
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Study of Resilience and Its Relationship with Academic and Work Dimensions during the COVID-19 Pandemic

Abstract: Background: The aim of the present study was to describe the resilience levels in a Spanish population during the Coronavirus (COVID-19) pandemic and to analyze the existing associations between high resilience and socio-demographic, work, and academic parameters. Method: 1176 individuals aged 18–67 years participated in a descriptive cross-sectional study. The participants were administered the 10-item resilience scale developed by Connor-Davidson (CD-RISC-10) and an ad-hoc questionnaire that collected inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Other studies, such as Ye et al [63], highlight the differences in adapting to the lockdown according to social context, support received, or situations of disability. San Román-Mata et al [64], in a study similar to the present one that also applied the Connor-Davidson Resilience Scale but in a non-university population, concluded that employed people, those with higher education, people working in emergency services and those with dependents presented higher rates of resilience.…”
Section: Resilience and Covidmentioning
confidence: 53%
“…Other studies, such as Ye et al [63], highlight the differences in adapting to the lockdown according to social context, support received, or situations of disability. San Román-Mata et al [64], in a study similar to the present one that also applied the Connor-Davidson Resilience Scale but in a non-university population, concluded that employed people, those with higher education, people working in emergency services and those with dependents presented higher rates of resilience.…”
Section: Resilience and Covidmentioning
confidence: 53%
“…Just as suggested regarding emotional stability, it may be that this result is explained by the generalized impact of the pandemic on individuals’ mood. Thus, resilience, although a personal and intrinsic feature, is also a dynamic psychological factor that can be malleable by the context ( Román-Mata et al, 2020 ). To our knowledge, this is the first study which analyzes the relationship between resilience and the efficacy of musical behavior for wellbeing enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…Resilience is a vital component in the optimal functioning of healthcare professionals [ 7 , 8 ], corporate leaders [ 9 ], military personnel [ 10 ], first responders [ 11 ], educationists [ 12 ], and the general community at large [ 13 ]. This is especially the case following stressful events such as the global 2019 coronavirus disease (COVID-19) pandemic caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%